Highly selective detection of methanol in aqueous and ethanol medium based on hybrid ZnS:Mn2+quantum dots/N-methylpolypyrrole as a fluorescence switchable sensor. (30th October 2020) - Abbasi, Fatemeh; Alizadeh, Naader
Highlights: Synthesis of new ZnS:Mn 2+ QDs-NMPPy hybrid as fluorescence switchable sensing system. Hybridization was caused a selective and sensitive fluorescence response to methanol. Successfully utilized to determine the amount of methanol in water and ethanol medium. Sensing mechanism of ZnS:Mn 2+ QDs/NMPPy hybrid is competitive interaction. Abstract: Methanol is highly toxic for human, so methanol detection is valuable especially in water and ethanol medium without complicated and time consuming procedure. In this work, we present a new fluorescence probe for direct detection of methanol in aqueous and ethanol medium based on the ZnS:Mn 2+ quantum dot (QDs) and soluble N-methylpolypyrrole (NMPPy) hybrid. Moreover, the number of spectroscopic techniques were used to study the chemical composition and optical properties of the resultant QDs as well as investigation on the sensing mechanism toward methanol. Also, methanol can be determined by using ZnS:Mn 2+ QDs/NMPPy hybrid based switchable fluorescence sensing system, with high sensitivity, high selectivity and a very good detection limit of 1 mM with linearity in the concentration range of 25–230 mM (~0.1–0.9% v/v) in aqueous solution. Finally, the ZnS:Mn 2+ QDs/NMPPy hybrid as optical sensor was successfully utilized to determine the amount of methanol in real alcoholic beverage samples.